2017
DOI: 10.1007/s00894-017-3510-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and theoretical studies of the interactions of a pyridyl-based corrosion inhibitor with iron clusters (Fe15, Fe30, Fe45, and Fe60)

Abstract: The capacity of 2,6-bis[((2-pyridylmethyl)oxy)methyl)]pyridine (BPMMP) to inhibit the corrosion of mild carbon steel in HCl was analyzed. In a polarization study, both the cathodic and anodic currents were appreciably decreased in the presence of BPMMP, suggesting that this ligand is effective at inhibiting corrosion at the metal surface. This conclusion is consistent with the results of impedance analysis, where only one time constant corresponding to one depressed capacitive loop was detected, and the diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…With the low resistivity feature of Ti 3 C 2 T x compared to the GCE, the overall conductivity of the modified working electrode ( MXene /GCE) drastically increases, leading to a high electron transfer. This also demonstrates the role of MXene as a conducting platform for charge transport in addition to serving as an active material for electrochemical reduction of 4-NP. Electrochemical analysis explicitly gives evidence that the chemically exfoliated Ti 3 C 2 T x MXene material is a highly desirable material for electrochemical reduction of 4-NP in the environment.…”
Section: Results and Discussionmentioning
confidence: 86%
“…With the low resistivity feature of Ti 3 C 2 T x compared to the GCE, the overall conductivity of the modified working electrode ( MXene /GCE) drastically increases, leading to a high electron transfer. This also demonstrates the role of MXene as a conducting platform for charge transport in addition to serving as an active material for electrochemical reduction of 4-NP. Electrochemical analysis explicitly gives evidence that the chemically exfoliated Ti 3 C 2 T x MXene material is a highly desirable material for electrochemical reduction of 4-NP in the environment.…”
Section: Results and Discussionmentioning
confidence: 86%
“…46 Moreover, this lower R ct value of the CuNi/IL@MWCNT modified GCE turned the system to be kinetically favorable. 43,47 Furthermore, to verify the EIS data, the electrochemical properties of CuNi/IL@MWCNTs/GCE have been investigated using CV at a scan rate of 100 mV s −1 shown in Fig. 3(B).…”
Section: Resultsmentioning
confidence: 99%
“…To date, a portion of the experimental results have not been well understood. On the theoretical side, many investigations have also been carried out to predict the geometry and electronic structures of iron clusters [44–65]. Recently, Dai et al found that small iron clusters have good catalytic activity and the Fe 13 cluster has an abnormally small thermal expansion [63–65].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the transition metals, iron is widely used in daily life and production, and has excellent properties in active agents, catalysts, and powder metallurgy. To further explore the physicochemical properties of iron substances, the iron clusters have been investigated both experimentally and theoretically [37–65]. On the experimental side, Nour et al reported the far‐infrared spectra of iron in Ar matrices at 12 K and the v 3 antisymmetric stretching frequencies of Fe 3 cluster was observed for the first time [37].…”
Section: Introductionmentioning
confidence: 99%